The Ontology of AI - An Aristotelian Analysis - Crespo, Ricardo F. (Acta Philosophica, 2024)
The aim of this paper is to examine the ontological nature of AI based on Aristotle’s metaphysical categories. It first provides a brief introduction to these categories and applies them specifically to artifacts, including AI. Next, it investigates whether an artifact like AI can actually think. To that end, it presents Aristotle’s understanding of thinking and concludes that, while AI can perform certain intellectual activities, it cannot attain an abstractive intuition of essences and causes. Consequently, AI is ‘nominalist’ and falls within a nominalist approach to ontology. The paper explores the implications of this perspective for AI’s ability to pursue the truth, as well as the corresponding notion of AI’s freedom.